State Support of Tourism and Recreation in Russia: Factors of Increasing Competitiveness, Risks, Development Prospects - Evgenia Anatolievna Kuklina (Управленческое консультирование)
The article examines the issues of state support for tourism and recreation in the Russian Federation in modern conditions. The dynamics of competitiveness index in travel and tourism sectors for the period 2007-2015 is given, as well as assumptions on the reasons for its positive dynamics are made. The main factors of increasing the competitiveness of the industry are formulated. It is concluded that an effective support from the state is necessary for positive changes in trends of its development. For the successful implementation of the state subprogram «Tourism» the following is of crucial importance: the forecasting of possible risks related to the achievement of the main goal and to the accomplishment of the tasks of the subprogram, an assessment of their scope and consequences, and the development of a set of measures of preventing of the latter. For the purpose of an effective risk management, a classification of risk factors is developed. Based on the analysis of possible risks, a classification of risks in tourism development is proposed. An objective function for managing the risks of implementing projects and programs is also proposed. A conclusion on the need for the implementation of regional projects in the tourism sector is substantiated. Such regional projects must take into consideration specific features of regions and shift of the paradigm in development of the subsystems «Culture» and «Tourism and Recreation».